PTH-017 Large proportions of patients with renal failure have significant upper gastrointestinal findings at endoscopy. Results from a tertiary referral centre. (23rd September 2015) - Butt, S K; Greenfield, S; Carter, M; Rowlands, D; Sargeant, I
Abstract : Introduction: The demand for endoscopy is ever increasing as is the rise in overall costs of endoscopy and waiting times. Adherence to appropriate indications is essential to prevent the rise in proportions of negative and hence unnecessary endoscopies. Patients with chronic renal impairment are one group of patients who may have significant gastrointestinal symptoms and often form an important number of referrals to the endoscopy unit for upper GI endoscopy. These patients are of variable complexity and often have multi-organ disease. Anaemia can often be the indication for referral despite this being part of the disease complex. We wanted to investigate the indications and endoscopic findings in renal patients from a busy tertiary referral centre. Methods: The aim was to assess the findings at gastroscopy in patients with renal failure from a renal tertiary referral centre. This was a single centre, retrospective analysis of renal patients who were referred for gastroscopy. Patient details were obtained from the CIPTS database by isolating patients under the named renal physician referrer. Gastroscopy reports between 2006 until April 2009 were obtained and analysed for indications and diagnosis at endoscopy. Results: A total of 90 gastroscopies in 73 patients were conducted during the study period. The age range was 45–92 and 58% were male patients. 86% of the gastroscopies were inpatient procedures. The majority of indications for gastroscopies included anaemia, haematemesis or melaena and these accounted for the indication 75 times either alone or in combination. Out of 90 gastroscopies 31 (34%) were considered as normal. Those gastroscopies in the normal category included reports of normal gastroscopies, hiatus hernias or minimal gastritis. All else was classed as abnormal (66%). Erosive lesions within the upper GI tract were diagnosed 47 times in the 90 reports (52%). These included oesophageal, gastric and duodenal ulcers, mallory weiss tears, duodenal erosions, and pyloric and duodenal stenoses. Three reports had cancer (1 duodenal, 2 oesophageal), and vascular lesions (angiodysplasia, telangiectasia, portal gastropathy, varices) were reported 14 (16%) times. Conclusion: Two-thirds of patients with renal failure referred for an upper GI endoscopy have abnormal findings. The majority have erosive disorders as opposed to vascular lesions as previously reported to be associated in the literature. Our study demonstrates a high pick-up rate of in-patients with renal failure and we recommend that the threshold to endoscopy in such patients should be low, and anaemia should not be ascribed to one of chronic disease without performing a gastroscopy.